Regulating polystyrene glass transition temperature by varying the hydration levels of aromatic ring/Li⁺ interaction - Chin, Sze Yuet (2024)
Polymer properties can be altered via lithium ion doping, whereby adsorbed Li+ binds with H2O within the polymer chain. However, direct spectroscopic evidence of the tightness of Li+/H2O binding in the solid state is limited, and the impact of Li+ on polymer sidechain packing is rarely reported. Here, we investigate a polystyrene/H2O/LiCl system using solid-state NMR, from which we determined a dipolar coupling of 11.4 kHz between adsorbed Li+ and H2O protons. This coupling corroborates a model whereby Li+ interacts with the oxygen atom in H2O via charge affinity, which we believe is the main driving force of Li+ binding. We demonstrated the impact of hydrated Li+ on sidechain packing and dynamics in polystyrene using proton-detected solid-state NMR. Experimental data and density functional theory (DFT) simulations revealed that the addition of Li+ and the increase in the hydration levels of Li+, coupled with aromatic ring binding, change the energy barrier of sidechain packing and dynamics and, consequently, changes the glass transition temperature of polystyrene.